Luteolin reduces fluid hypersecretion by inhibiting TMEM16A in interleukin-4 treated Calu-3 airway epithelial cells - Kim, Hyun Jong; Woo, JooHan; Nam, Yu-Ran; Seo, Yohan; Namkung, Wan; Nam, Joo Hyun; Kim, Woo Kyung (The Korean journal of physiology & pharmacology, 2020)
Rhinorrhea in allergic rhinitis (AR) is characterized by the secretion of electrolytes in the nasal discharge. The secretion of Cl- and HCO3- is mainly regulated by cystic fibrosis transmembrane conductance regulator (CFTR) or via the calciumactivated Cl- channel anoctamin-1 (ANO1) in nasal gland serous cells. Interleukin-4 (IL-4), which is crucial in the development of allergic inflammation, increases the expression and activity of ANO1 by stimulating histamine receptors. In this study, we investigated ANO1 as a potential therapeutic target for rhinorrhea in AR using an ANO1 inhibitor derived from a natural herb. Ethanolic extracts (30%) of Spirodela polyrhiza (SPEtOH) and its five major flavonoids constituents were prepared. To elucidate whether the activity of human ANO1 (hANO1) was modulated by SPEtOH and its chemical constituents, a patch clamp experiment was performed in hANO1-HEK293T cells. Luteolin, one of the major chemical constituents in SPEtOH, significantly inhibited hANO1 activity in hANO1-HEK293T cells. Further, SPEtOH and luteolin specifically inhibited the calcium-activated chloride current, but not CFTR current in human airway epithelial Calu-3 cells. Calu-3 cells were cultured to confluency on transwell inserts in the presence of IL-4 to measure the electrolyte transport by Ussing chamber. Luteolin also significantly inhibited the ATP-induced increase in electrolyte transport, which was increased in IL-4 sensitized Calu-3 cells. Our findings indicate that SPEtOH- and luteolin may be suitable candidates for the prevention and treatment of allergic rhinitis. SPEtOH- and luteolin-mediated ANO1 regulation provides a basis for the development of novel approaches for the treatment of allergic rhinitis-induced rhinorrhea.Rhinorrhea in allergic rhinitis (AR) is characterized by the secretion of electrolytes in the nasal discharge. The secretion of Cl- and HCO3- is mainly regulated by cystic fibrosis transmembrane conductance regulator (CFTR) or via the calciumactivated Cl- channel anoctamin-1 (ANO1) in nasal gland serous cells. Interleukin-4 (IL-4), which is crucial in the development of allergic inflammation, increases the expression and activity of ANO1 by stimulating histamine receptors. In this study, we investigated ANO1 as a potential therapeutic target for rhinorrhea in AR using an ANO1 inhibitor derived from a natural herb. Ethanolic extracts (30%) of Spirodela polyrhiza (SPEtOH) and its five major flavonoids constituents were prepared. To elucidate whether the activity of human ANO1 (hANO1) was modulated by SPEtOH and its chemical constituents, a patch clamp experiment was performed in hANO1-HEK293T cells. Luteolin, one of the major chemical constituents in SPEtOH, significantly inhibited hANO1 activity in hANO1-HEK293T cells. Further, SPEtOH and luteolin specifically inhibited the calcium-activated chloride current, but not CFTR current in human airway epithelial Calu-3 cells. Calu-3 cells were cultured to confluency on transwell inserts in the presence of IL-4 to measure the electrolyte transport by Ussing chamber. Luteolin also significantly inhibited the ATP-induced increase in electrolyte transport, which was increased in IL-4 sensitized Calu-3 cells. Our findings indicate that SPEtOH- and luteolin may be suitable candidates for the prevention and treatment of allergic rhinitis. SPEtOH- and luteolin-mediated ANO1 regulation provides a basis for the development of novel approaches for the treatment of allergic rhinitis-induced rhinorrhea.